Risk And Return Characteristics Of Indonesian Banking Stocks During The COVID-19 And Post-Pandemic Period: A Descriptive Quantitative Analysis - Nidrah (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study examines the risk and return characteristics of selected banking stocks listed on the Indonesia Stock Exchange during the period 2020–2025, covering the COVID-19 crisis, recovery phase, and post-pandemic adjustment period. A descriptive quantitative approach was employed using secondary data obtained from Investing.com. The sample consists of ten banking stocks, namely BBCA, BBRI, BMRI, BBNI, BRIS, BBTN, BNGA, BNLI, NISP, and MEGA. Descriptive statistics were selected because the study aims to provide an empirical mapping of stock return characteristics without testing causal relationships. The analysis includes mean return, minimum return, maximum return, and standard deviation. The findings indicate that all sampled banking stocks generated positive average monthly returns, although substantial differences exist in risk and volatility profiles. BRIS recorded the highest average return and volatility, while BNLI exhibited the highest maximum return. NISP and BBCA showed relatively stable performance with lower volatility. These results suggest that Indonesian banking stocks possess heterogeneous risk-return characteristics despite operating within the same sector. The study provides practical implications for investors in constructing banking stock portfolios based on risk preferences and return expectations. However, the findings are limited to descriptive analysis and do not investigate the determinants of stock returns. Future studies may incorporate risk-adjusted performance measures and causal modeling approaches.